Endoscopic Drainage of Intra-abdominal Fluid Collections and Abscesses - Chittajallu, Vibhu; Adoor, Dayyan; Faulx, Ashley L. (Seminars in Interventional Radiology, 2024)
Endoscopic ultrasound (EUS) has transitioned from a primarily diagnostic to a therapeutic procedure. EUS-guided drainage of intra-abdominal fluid collections is common practice with vast data in the management of symptomatic, mature pancreatic fluid collections. Evidence has demonstrated that EUS-guided drainage for these intra-abdominal fluid collections is effective with an acceptable safety profile. These techniques are being utilized for the management of other intra-abdominal fluid collections with equally positive results. This review will discuss the utilization of EUS for the management of various intra-abdominal fluid collections, discussing efficacy, safety, and limitations.
Keywords: endoscopic ultrasound; gastroenterology; intra-abdominal fluid collections; abscess; interventional radiology